Improving the ability to analysis social phenomenons with the interdisciplinary approach of the group investigation model - Fahmi Imron, Ilmawati (Universitas Nusantara PGRI Kediri, 2022)
Abstract: Based on the observation results of social studies learning materialon social phenomena at PGSD UN PGRI Kediri, it can be concluded that most students are less responsive to problems that occur in society in an interdiciplinary manner. This will reduce the meaning of learning social science. Based on some of these shortcomings then classroom action research (CAR) is carried out by applying an interdisciplinary approach and the learning Group Investigation model, because this learning model requires students to be more active in developing their attitudes and knowledge about social studies learning, especially social phenomena material that is in accordance with their respective abilities in constructing their own knowledge. This research design uses Classroom Action Research (CAR) with the stages of planning, implementing, observing and reflecting. The subject of this study were students of PGSD UN PGRI Kediri class 2B, odd semester of the 2019/2020 academic year. The data taken in this study are data from the results of investigation reports and learning outcomes data in the form of tests on the assessment sheet. The results obtained after applying an interdisciplinary approach with the Group Investigation model on the material of social phenomena, namely learning have been successful. It is evident in the results of student performance that there has been an increase from the first cycle, namely the average score is 74.4 and the second cycle the average score is 89.3. Then the student learning outcomes also experienced an increase in scores, namely from the first cycle with an average score of 79.5 and the second cycle average score of 94.